IMPLEMENTASI PROBLEM BASED LEARNING TERINTEGRASI KETERAMPILAN SOSIAL EMOSIONAL UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS V DI SD NEGERI PALEBON 03 - Setiawati, Indra; Joko Sulianto; Sadiyo; Dina Prasetyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to enhance the engagement of fifth-grade students at SD Negeri Palebon 03 through the implementation of a Problem-Based Learning (PBL) model integrated with Social Emotional Skills (SES). The problem addressed is the low level of positive interaction and student involvement during learning activities. The research methodology used is Classroom Action Research (CAR), conducted in two cycles, each consisting of two meetings. Each cycle involved planning, implementation, observation, and reflection. The results of the study showed a significant increase in various student activities such as visual, oral, listening, writing, drawing, motoric, mental, and emotional. In the first cycle, visual participation reached 76%, while in the second cycle it increased to 88%. Oral activity increased from 43% to 80%, listening from 67% to 76%, writing from 58% to 73%, drawing from 46% to 70%, motoric from 48% to 76%, mental from 55% to 79%, and emotional from 58% to 79%. In conclusion, the implementation of the PBL model integrated with SES is effective in increasing student engagement during learning activities.